To eat or not to eat, that is a question / Elyssa Maisara Ahmad Russlin and Nor Farawahidah Mohd Khamis - Ahmad Russlin, Elyssa Maisara; Mohd Khamis, Nor Farawahidah (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2023)
Eating, consuming, famish, full, or whatever it may be, does it concern only your taste palette? Do you think that 'disgust' would only be the taste of the food? Not how you felt or feel about it? My article will be focusing on understanding the act of 'disgust' in choosing food. According to Charles Darwin (1859), the act of disgust is when a human rejects or has a sense of revulsion for a particular event or something that was considered as bad, not tasteful, or offensive. The definition is also supported by Paul Rozin (2014) in the perspective of food-related emotion. Furthermore, as mentioned in Santisi et al (2021) study, neophobia and food disgust are both frequently related to negative attitudes towards food. Food disgust is the rejection of food that is thought to be potentially damaging to health, whereas neophobia is the propensity to avoid eating unfamiliar foods. Hence, when we discuss food upon the act of disgust, does it solely rely on the taste and not the memories, or even maybe the symbolic meanings attached to the time when you ate the food? A chapter of a book written by Patricia Pliner and Sarah-Jeanne Salvy (2006) discussed the 5 main substructures executed by Paul Rozin that supported the act of rejection of food choice.